MEASUREMENT OF YTTRIUM-90 BIODISTRIBUTION IN SELECTIVE INTERNAL RADIATION THERAPY (SIRT) - Sita Gandes Pinasti (Indonesian Journal of Physics and Nuclear Applications, 2019)
Measurement of radionuclides biodistribution in post-radioembolization 90Y SIRT is a part of treatment evaluation, in which the assessment of biodistribution is used to evaluate the possible extrahepatic presence and the absorbed dose estimation for the tumor cells, healthy liver cells, and critical organs. As the dose-response analysis is performed based on this evaluation, the biodistribution measurement coming from post-imaging modality has a crucial role in achieving these goals. The two devices, Single Photon Emission Tomography (SPECT) and Positron Emission Tomography are discussed in some aspects, including the quality of quantitative images, performance characteristics, and absorbed dose considerations.